Information Security Practice and Experience c - Bao, Feng.; Weng, Jian.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 7th International Conference on Information Security Practice and Experience, ISPEC 2011, held in Guangzhou, China, in May/June 2011. The 26 papers presented together with 6 short papers were carefully reviewed and selected from 108 submissions. They are grouped in sections on public key encryption, cloud security, security applications, post-quantum cryptography and side-channel attack, block ciphers and MACs, signature, secrete sharing and traitor tracing, system security and network security, and security protocols.
Keywords: Computer science; Computer Communication Networks; Data protection; Data encryption (Computer science).; Information storage and retrieval systems; Information Systems; Computer Science; Data Encryption; Systems and Data Security; Computer Communication Networks; Information Storage and Retrieval; Computers and Society; Management of Computing and Information Systems